SERVICE BLUEPRINT TERMINAL KARGO BANDARA SOEKARNO HATTA (Studi Kasus: PT Angkasa Pura II) - Siska Amonalisa Silalahi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
The cargo growth in Soekarno Hatta International Airport is quite significant (70.7 %) which still could be handled in warehouse with 49.956 m2 area. This condition make the warehouse is fully loaded or even overloaded. PT. Angkasa Pura II has projected that the cargo is still growing in the future. In 2023, the cargo will reach 1.500.000 ton which needs 115.552 m2warehouse area. Cargo handling is always related to blueprint service of giving cargo services in Soekarno Hatta which really needs to be re-designed. The re-designed of blueprint service will always perform the complexity of cargo handling services due to many divisions handling the cargo. The purpose of this study is to find out the on-going process of blueprintservice at the airport, to analyse the complexity of cargo handling and to re-design the blueprint service in cargo terminals of Soekarno Hatta International Airport. The study used the blueprint service (the fifth type of service re-design) and analysis of design distribution network by evaluating the customer needs and the cost needed to fulfill the customer needs.